L’induismo e l’antico sentiero dalla Bahakti yoga - Giuliano, Salvatore (Alpha Omega, 2014)
Summary: The Indian religious message put forward in the 20th century by the neo-Hindu mission has produced an enthusiastic consensus in the West, especially because what is pro-posed is not linked to any form of hierarchical subordination in a way which is perceived as excessive in Christianity. Religious elements extraneous to our religious tradition, such as re-incarnation, a sacral vision of the cosmos, a-personal divinity have been received on the basis of curiosity and of wonder according to modern sensitivity. This article offers a general panorama of the visions of God and of the human being implicit in Hindu spirituality and mysticism, and draws attention to the differences in regard to the development of Christian mysticism.Key words: Hindu mysticism, vision of God in Hinduism, vision of the human being in Hin-duism, mysticism of the bhakti.Parole Chiave: Mistica induista, visione di Dio nell’induismo, visione dell’uomo nell’induis-mo, mistica della bhakti.